Psychological Healing process of Grief Resolution: Nepali (Hindu) Cultural Perspective - Risal, Ajay (Bodhi: An Interdisciplinary Journal, 2024)
Grief is a natural reaction to the loss; mainly due to the death of a loved one. Sometimes, such reactions may be problematic or complicated. Culture serves as a buffer to deal with such losses, and supports the mature way of coping. Nepali cultural practices or the death rituals favor the restoration-oriented grieving process and are prophylactic approach in order to prevent any form of grief-related psychological reactions. This paper provides a narrative approach in which the writer shares his experiences as a Psychiatrist in dealing with grief-related problems of the clients in his own clinical practice. In addition, he also shares his own personal experience of losing his father and illustrates how the traditional practices followed by himself and his family during that time facilitated the grief-resolution process. He is very much convinced that the Nepali cultural approach during death rituals is very much scientific and psychotherapeutic.